Confirmatory Factor Analysis of the Sustainable Development Goals Derived Gentrification Scale in the Context of the Pandemic - Crespo, Julio E.; Lirios, Cruz García; Campas, Celia Yaneth Quiroz; Sánchez, Arturo Sánchez; Medina, Jorge E. Chaparro; Rodríguez, Isabel Cristina Rincón (Journal of Ecohumanism, 2024)
In the context of human development goals, gentrification has emerged as a significant and unpredictable phenomenon amid the ongoing health crisis, potentially impacting the sustainable development goals (SDGs). This study aimed to analyze the theoretical framework of gentrification and its empirical indicators in the unique context of the pandemic, foreseeing potential risk scenarios. A cross-sectional, psychometric, and correlational study was conducted with 100 university students dedicated to the SDGs during the pandemic. The findings revealed the prevalence of two out of seven factors associated with poverty alleviation and institutional justice for peace. Given the observation of seven factors in the current literature, this study recommends expanding the indicators to enhance the variance percentage and aligning the theoretical model with empirical evidence. It underscores the pressing need for collaborative efforts in urban and sustainable development.